1984
DOI: 10.3168/jds.s0022-0302(84)81341-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Sodium Bicarbonate and Calcium Chloride on Physiological Responses of Lactating Dairy Cows in Hot Weather

Abstract: Twenty-four lactating cows were assigned randomly to three treatments to evaluate responses to large differences of dietary sodium and chloride. Treatments were corn-cottonseed meal-corn silage based complete rations with either: 1) .23% sodium chloride (control), 2) control plus 2.28% calcium chloride, or 3) control plus 1.70% sodium bicarbonate. Treatment effects were significant for urine pH (7.96, 5.41, 8.18), blood pH (7.50, 7.39, 7.49), partial pressure of oxygen (91.2, 99.4, 86.3 mm Hg), partial pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
1
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 6 publications
9
34
1
2
Order By: Relevance
“…When cattle are heat stressed, excessive panting increases plasma pH and bicarbonate, reduces blood buffering capacity, and increases urinary excretion of sodium and bicarbonate ion (Sparke et al 2001). The K and KNa diets had elevated DCAD levels, which may be more important for maintaining blood pH than individual elements (Escobosa et al 1984;Wildman et al 2007;Ross et al 1994a, b). Reduced DCAD may induce mild metabolic acidosis (Vagnoni and Oetzel 1998), which may result in more severe acidosis when feedlot cattle are exposed to an increased heat load.…”
Section: Discussionmentioning
confidence: 95%
“…When cattle are heat stressed, excessive panting increases plasma pH and bicarbonate, reduces blood buffering capacity, and increases urinary excretion of sodium and bicarbonate ion (Sparke et al 2001). The K and KNa diets had elevated DCAD levels, which may be more important for maintaining blood pH than individual elements (Escobosa et al 1984;Wildman et al 2007;Ross et al 1994a, b). Reduced DCAD may induce mild metabolic acidosis (Vagnoni and Oetzel 1998), which may result in more severe acidosis when feedlot cattle are exposed to an increased heat load.…”
Section: Discussionmentioning
confidence: 95%
“…Excessive panting increases plasma pH and bicarbonate, reduces blood buffering capacity, and increases urinary excretion of sodium and bicarbonate ion (Sparke et al, 2001). The dietary cation-anion difference (DCAD) may be more important than the content of the individual elements (Escobosa et al, 1984). Reduced DCAD may induce mild metabolic acidosis (Vagnoni and Oetzel, 1998), and this may act as a trigger for more severe acidosis when feedlot cattle are exposed to an increased heat load.…”
Section: Discussionmentioning
confidence: 99%
“…These results agreed with those of Rogers et al (1982) which indicated that Na and K exert alkalogenic effects and Cl an acidogenic effect on the acid-base balance (Cohen et al, 1972). Escobosa et al (1984) fed dairy cows a diet containing 1.67% Cl during moderate heat stress and recorded lowered blood pH and urine pH compared with a control diet (34% Cl). Such results were consistent with Schneider et al (1988) who also measured higher concentrations of K in the rumen, but Na concentrations were not increased by a diet high in minerals.…”
Section: Mineral Metabolismmentioning
confidence: 99%